City Mapping and Leading Creative Industry Sub Sectors as the Basis of City Branding Policy in Central Java - Sulistyorini, Utami Tri; Amid, Jusmi -; Widiyati, Sri - (Politeknik Negeri Semarang, 2020)
The research is aimed to gain a map of the cities/districs and the competitive advantage of creative industry sectorsÂ as a base of city branding. In order to achieve this goal, secondary data from BPS and Bekraf are used. There are 15 creative industry sectors in 35 Cities of Central Java.These data are analysed by using three methods, those are ShiftShare, Location Quotient, and Specialization Indices.ShiftShare analysis is employed to map the competititve advantage of creatice industry sectors in Central Jawa. While Location Quotient, and Specialization Indicesare used to map cities/districts in Central Java which has a competitive advantage to empower the creative industry (results of shift share analysis).The analisys results show that Surakarta City, Demak District and Magelang District have ability to empower their creative industry sectors to push their economic growth.The results also show that Klaten District which is a transit district of the two center tourism city (Surakarta and Yogyakarta), their manufacture sectors have a positive competitve shift andÂ biggest contribution for their economic growth. Acomodation and beverages, information and communications, also company service are the primacy creative industry sectors of Surakarta City and Magelang District. While trade is the primacy creative industry sector of Demak District